Cost‐effectiveness of electronic‐ and clinician‐delivered screening, brief intervention and referral to treatment for women in reproductive health centers. (28th June 2019) - Olmstead, Todd A.; Yonkers, Kimberly A.; Ondersma, Steven J.; Forray, Ariadna; Gilstad‐Hayden, Kathryn; Martino, Steve
Abstract: Aims: To determine the cost‐effectiveness of electronic‐ and clinician‐delivered SBIRT (Screening, Brief Intervention and Referral to Treatment) for reducing primary substance use among women treated in reproductive health centers. Design: Cost‐effectiveness analysis based on a randomized controlled trial. Setting: New Haven, CT, USA. Participants: A convenience sample of 439 women seeking routine care in reproductive health centers who used cigarettes, risky amounts of alcohol, illicit drugs or misused prescription medication. Interventions: Participants were randomized to enhanced usual care (EUC, n  = 151), electronic‐delivered SBIRT (e‐SBIRT, n  = 143) or clinician‐delivered SBIRT (SBIRT, n  = 145). Measurements: The primary outcome was days of primary substance abstinence during the 6‐month follow‐up period. To account for the possibility that patients might substitute a different drug for their primary substance during the 6‐month follow‐up period, we also considered the number of days of abstinence from all substances. Incremental cost‐effectiveness ratios and cost‐effectiveness acceptability curves determined the relative cost‐effectiveness of the three conditions from both the clinic and patient perspectives. Findings: From a health‐care provider perspective, e‐SBIRT is likely (with probability greater than 0.5) to be cost‐effective for any willingness‐to‐pay value for an additional day of primary‐substance abstinence and an additional day of all‐substance abstinence. From a patient perspective, EUC is most likely to be the cost‐effective intervention when the willingness to pay for an additional day of abstinence (both primary‐substance and all‐substance) is less than $0.18 and e‐SBIRT is most likely to be the cost‐effective intervention when the willingness to pay for an additional day of abstinence (both primary‐substance and all‐substance) is greater than $0.18. Conclusions: e‐SBIRT could be a cost‐effective approach, from both health‐care provider and patient perspectives, for use in reproductive health centers to help women reduce substance misuse.